Identification of training needs in schistosomiasis research to build capacity for schistosomiasis control in Uganda - Damalie Nakanjako; Moses Egesa; Helen Byakwaga; Casim Umba Tolo; Anatol Maranda Byaruhanga; Prudence Beinamaryo; Grace Banturaki; Lydia Nakiyingi; Ponsiano Ocama; Moses R. Kamya; Alison M. Elliott (Tropical Medicine & International Health, 2025)
Background: Schistosomiasis is the leading cause of fatal upper gastrointestinal bleeding among adults in East Africa. The prevalence among school-aged children in villages along the Albert–Nile shoreline in North-Western Uganda is estimated at 85%. Efforts to control schistosomiasis in low- and-middle-income countries remain limited due to an incomplete understanding of the pathogenesis, disease manifestations, transmission mechanisms, preventive measures and interventions. In addition, there is insufficient capacity to analyse, model and predict relevant clinical case management systems, biological interventions and disease control efforts. We conducted a needs assessment for schistosomiasis research training at academic and research institutions in Uganda to inform the development of a structured training programme to build capacity to conduct locally relevant research to control the disease. Methods: Using an online survey, we collected data on training needs, potential trainees, available resources including local and international collaborations, as well as priority areas for schistosomiasis research and training at academic and research institutions in Uganda. Data were analysed and presented in frequency tables and figures. Results: Overall, schistosomiasis had the lowest number of studies conducted, based on the studies approved by research ethics committees at the two leading medical schools in Uganda: Makerere University College of Health Sciences (MakCHS) and Mbarara University of Science and Technology (MUST) between 2016 and 2022. The top ranked schistosomiasis focus areas of interest, by scientists at MakCHS, MUST, the Vector Borne and Neglected Tropical Diseases Division of the Ministry of Health and the Uganda Virus Research Institute (UVRI), were schistosomiasis prevention and transmission, vector biology, diagnostics, treatment and clinical trials, respectively. The top ranked training needs were schistosomiasis prevention and control, research ethics, data analysis, epidemiology and research methods (quantitative and qualitative), malacology, infectious diseases modelling, scientific writing and communication skills. Conclusion: Priority areas for schistosomiasis research and training will be utilised to develop a robust, collaborative, multidisciplinary schistosomiasis research training programme, to increase the critical mass of scientists with the competencies required to design, execute and utilise schistosomiasis biology, clinical, laboratory and epidemiology research to advance disease control interventions and minimise/eliminate schistosomiasis-associated morbidity and mortality in sub-Saharan Africa.
Keywords: Capacity building; Malacology; Research training; Schistosomiasis; Sub-Saharan Africa; Uganda